Literasi Digital: Revitalisasi Inovasi Teknologi - Ahmad Rohman; Masduki Asbari; Dimas Rezza (Journal of Information Systems and Management (JISMA), 2024)
The aim of this study is to encourage people to always have the latest information and be ready to adapt to technological developments. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to oral narratives from the BukaTalks Bukalapak Youtube channel entitled "Empowering Society Through Digital Media". The results of this study explain that the world continues to change, in the past when we needed something, we had to look for it and come to the place we needed it, but in this era of the digital revolution, this can be easily obtained without us leaving the place. Indeed, the Digital Revolution in this information era is able to improve relationships. There is no choice to change according to technology. Technology is the key. If we don't master technology, we will be left behind. But the problem is again, today we master one technology, the next second there could be a new technology. This means that what is needed is not technical things, but the ability to continue learning new things. "Life long learner abilities are what will make us relevant wherever and whenever."